Innovative GMPPT searching algorithm and precise backstepping control for grid-connected PV system in challenging shading environments - Bahri, Mohamed; Talea, Mohamed; Bahri, Hicham; Aboulfatah, Mohamed (Institute of Advanced Engineering and Science, 2024)
Photovoltaic (PV) systems encounters different problems of weather conditions that lowers their generated power. For this reason, maximum power point tracking (MPPT) have been designed to track the maximum power at all times and thus minimize these losses. However, under complexes partial shading condition (PSC) these losses are even higher. Classical MPPT algorithms fails to track the global MPP (GMPP) which further augment the power losses. Alternately, a grid connected topology of the PV system is chosen but needs a control method to phase the inverter current with the grid. This paper introduces a novel algorithm named power search algorithm (PSA) that memorizes the highest peak as it scans the PV curve then returns and locks it. Due to its simplicity, this proposed method is suitable for practical use and manages to track the GMPP with high efficiency of 99.5% and a mean response time of 0.04 s. Comparison was made with a gray wolf optimization (GWO) technique. Simulation was done in MATLAB/Simulink. Results shows that the proposed algorithm performed better than the GWO in all aspect of efficiency, tracking time and oscillations around GMPP. Also, a backstepping control was used to inject a good synchronized power to the grid.